МОДЕЛЮВАННЯ ЕЛЕКТРОМАГНІТНИХ ПРОЦЕСІВ БЕЗДРОТОВОЇ ЗАРЯДКИ ЄМНІСНОГО НАКОПИЧУВАЧА НА ОСНОВІ ТРАНСФОРМАТОРА ТЕСЛИ - Ломко, М.О. (Інститут електродинаміки Національної академії наук України, 2024)
The processes of wireless high-voltage energy storage using a Tesla resonant transformer were studied on working experimental samples. Modeling of charging links with a Latour circuit and a bridge rectifier was carried out. The prospects of using the developed models for correcting the parameters of charging devices are determined. Ref. 10, fig. 5.